Preliminary evidence on internal migration, remittances, and teen schooling in India - Mueller, Valerie; Shariff, Abusaleh (International Food Policy Research Institute, 2009)
Migration can serve as an outlet for employment, higher earnings, and reduced income risk for households in developing countries. We use the 2004–2005 Human Development Profile of India survey to examine correlations between the receipt of remittances from internal migrants and human capital investment in rural areas. We employ a propensity score–matching approach to account for the selectivity of households into receiving remittances. We interpret the results conservatively due to the cross-sectional nature of the data. We find a positive correlation between remittances received from internal migrants and the schooling attendance of teens. The magnitude of the correlation is greater when focusing on low-caste households, and male schooling attendance in particular becomes more positive and statistically significant. Our findings provide a basis for establishing future research in the areas of migration and social protection in India.